Evaluasi Dampak Program Rumah Susun Lette Kecamatan Mariso Kota Makassar - Ramlah, Ramlah; Tahir, Muh; Ma'ruf, Adnan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine the evaluation of the impact of the lette rental apartment program in Mariso District, Makassar City. This study used a qualitative method to describe and explain the evaluation of the impact of the rental apartment program. The number of informants in this study were 8 people. The results of the study showed that the evaluation of the impact of the lette rental apartment program Mariso District of Makassar had a number of very significant effects ranging from economic impacts on equity indicators, political impacts on effectiveness indicators and social impacts on responsiveness indicators. Therefore, the hypothesis in the study was accepted because it was supported by the significance value. Furthermore, the evaluation of the impact of the rental apartment program was also influenced by factors of equity, effectiveness and responsiveness. Keywords: equity, effectiveness, responsiveness